A digital learning program in handball legal knowledge for female students of the College of Physical Education and Sports Sciences - Al-Shammari, Prof. Dr. Fadhil Kurdi; Kurdi, Asst.L.Hamam Fadel; Shaker, Prof. Dr. Khaled (Sulaimani Journal for Humanities, 2026)
The importance of this research lies in identifying the legal knowledge of female students in the College of Physical Education and Sports Sciences, and subsequently improving their abilities to reach a level that qualifies them to officiate matches. The research problem is that improving and developing the legal knowledge of handball among female students requires introducing them to the cognitive, skill-based, and technical aspects in order to prepare them for officiating matches. As the researchers are specialists and teachers in handball at the college, they found no program to develop the legal knowledge of female students, nor any applications or websites that could help develop this knowledge. Therefore, this research aims to utilize a digital learning program to enhance the legal knowledge of female students in the College of Physical Education and Sports Sciences and to identify their existing legal knowledge. The researchers hypothesized that there is a positive effect of the digital communication educational program on the legal knowledge of female students at the College of Physical Education and Sports Sciences. The researcher used the experimental method with a single experimental group with pre- and post-tests to suit the nature of the problem to be solved. The researchers defined the research sample as (18) female students from the College of Physical Education and Sports Sciences, and selected (10) female students for the experimental group. The researchers used a digital communication program, and after its application, the post-test was conducted. From it, the data was extracted and statistically analyzed in order to achieve the research objectives, and then the results were presented, analyzed, and discussed. The researchers concluded that digital communication between the students and the rules of handball, along with ease of use and browsing, greatly improved the students' legal knowledge. Explaining some legal materials and making them available in video format helped the sample improve their legal knowledge. Also, the possibility of reviewing lectures at any time through links to the recording of each lecture was also noted. Based on the above, the researchers recommended focusing on continuous digital communication with the student and relying on signals and how to perform them, as well as their synchronization with the whistle, which helps the student succeed in leading the match. One of the most important things is following up with the students, and the digital communication program created the possibility of following up and improving the students' knowledge of legal knowledge. It is necessary to use educational programs with digital communication in designing programs for the rules of different games.
Keywords: Digital communication; Legal knowledge